A wall crack repair material and repair process

Through the method of combining water-based permeable inorganic waterproofing agent and a U-shaped sealing strip or water-absorbing resin-type curing film, the problems of low strength and poor durability of concrete crack repair materials in the prior art are solved, and deep penetration of narrow cracks and Enclosed, has permanent waterproof and impermeability and simplicity of construction.

CN116573917BActive Publication Date: 2024-12-27WUHAN YUANJIN BUILDING MATERIALS TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310350580.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2024-12-27
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

When repairing concrete cracks, existing building materials have problems such as low strength, poor durability and difficulty in seeping into narrow cracks, and cannot achieve permanent repair.

Method used

A water-based osmotic inorganic waterproofing agent is composed of alkali metal silicate aqueous solution, osmotic crystallization functional additive, etc. The permeability and crystallization are promoted through osmotic crystallization functional additive, and the alkali metal silicate aqueous solution reacts with Ca(OH)2 Inorganic crystals are generated, cracks are blocked, and deep penetration and sealing of cracks are achieved through the combination of U-shaped plastic sealing strips or water-absorbing resin-type curing films.

Benefits of technology

It realizes effective repair of cracks in concrete walls below 0.4mm. The generated inorganic crystals have the same lifespan as concrete, have permanent waterproof and impermeability, and are simple to construct and do not affect the appearance of the wall.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004161367370000011
    Figure HDA0004161367370000011
  • Figure HDA0004161367370000012
    Figure HDA0004161367370000012
Patent Text Reader

Abstract

The invention discloses a wall crack repair material, which is a water-based penetrating inorganic waterproofing agent, comprising, by mass percentage, 30-50wt% of an alkali metal silicate aqueous solution and 0.2-5wt% of a penetrating crystallization functional auxiliary agent, and the rest being water; wherein the alkali metal silicate aqueous solution is selected from at least two of a sodium silicate aqueous solution with a mass fraction of 30-40%, a potassium silicate aqueous solution with a mass fraction of 30-40%, or a lithium silicate aqueous solution with a mass fraction of 20-30%, and the like; and the penetrating crystallization functional auxiliary agent comprises, by mass percentage, 55-65% of EDTA-4Na, 15-25% of triethanolamine, 5-15% of citric acid, 6-10% of sodium polyacrylate, and 1-3% of sodium dodecylbenzene sulfonate. When repairing wall cracks, first clean the wall at the cracks, remove dust, dirt and loose parts on the surface, repair and smooth the roughness, pits and other defects with cement-based materials, and then use U-shaped sealing strips, water-absorbent resin curing films or a combination of the two to repair the cracks or fissures on the wall.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials and construction, and in particular to a wall crack repairing material and a repairing process. Background Art

[0002] In construction and municipal underground projects, shear walls are prone to top-to-bottom through-cracks or small-scale radial fine cracks due to factors such as load, concrete temperature shrinkage and drying shrinkage, which can easily cause leakage, reduce the durability of reinforced concrete, and affect structural safety. In engineering practice, polyurethane, acrylic, epoxy resin or polyurea grouting repair is usually used to plug concrete cracks. The above grouting liquids are organic filling materials with disadvantages such as low strength or poor durability. They can plug leaks but cannot permanently repair concrete cracks. Cement-based grouting materials can also be used as crack repair materials. They are inorganic materials with good concrete bonding and durability, but they are difficult to inject into narrow cracks with a width of 0 to 0.5 mm. Therefore, how to obtain a repair process that is simple to construct and has good durability is a problem that the inventors have considered. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a wall crack repair material and repair process in view of the deficiencies of the above-mentioned prior art. The repair material of the present invention has the functions of penetration crystallization and secondary crystallization, and can penetrate deep into the concrete cracks and penetrate 4 to 5 cm into the concrete, and crystallize deeper into the cracks, gradually sealing the cracks from the inside to the outside.

[0004] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0005] A wall crack repair material, which is a water-based penetrating inorganic waterproofing agent, comprises, by mass percentage, 30-50wt% of an alkali metal silicate aqueous solution, 0.2-5wt% of a penetrating crystallization functional auxiliary agent, and the remainder is deionized water; wherein the alkali metal silicate aqueous solution is selected from at least two of a 30-40% sodium silicate aqueous solution, a 30-40% potassium silicate aqueous solution, or a 20-30% lithium silicate aqueous solution; and the penetrating crystallization functional auxiliary agent comprises, by mass percentage, 55-65% EDTA-4Na, 15-25% triethanolamine, 5-15% citric acid, 6-10% sodium polyacrylate, and 1-3% sodium dodecylbenzene sulfonate.

[0006] By adopting the above technical solution, the alkali metal silicate aqueous solution as a crystal component can react with Ca(OH)2 inside the wall cracks to crystallize and plug the cracks. The generated crystals are inorganic crystals with good durability and can have the same life as the structure. The penetrating crystallization functional additive plays an auxiliary role in the crack repair process, including promoting penetration, assisting crystallization, and complexing Ca 2+, improve crystal strength, adjust gel time, etc. Among them, sodium silicate is the most commonly used crystal material for reaction crystallization, and its cost is also the lowest; the secondary crystal strength of the material solidified by potassium silicate is the highest, which can significantly improve the secondary self-repair effect of cracks; the film-forming material after lithium silicate solidification has good water resistance, which can significantly improve the impermeability and durability of concrete; EDTA-4Na is a strong chelating agent that can chelate Ca in concrete at the cracks. 2+ , promoting the formation of reaction crystals; triethanolamine can improve the internal structure of the generated crystals and increase the strength of the crystals; citric acid can adjust the gel time of the repair material; sodium polyacrylate uses a substance with a molecular weight of 8000, which can adjust the consistency of the repair material to make it suitable for repairing wider cracks. At the same time, sodium polyacrylate itself can also react with Ca 2+ Reaction crystallization; Sodium dodecylbenzene sulfonate acts as a surfactant to reduce the surface tension of the repair material and promote penetration.

[0007] According to the above scheme, the mass fractions of the alkali metal silicate solution and the infiltration crystallization functional additive in the repair material vary with the width of the wall crack, as follows:

[0008] A) When the crack width is less than 0.2 mm, 30-40 wt% of alkali metal silicate aqueous solution, 0.2-4 wt% of infiltration crystallization functional additive, and the balance of deionized water;

[0009] B) When the crack width is greater than 0.2 mm and less than 0.4 mm, 40-50 wt% of alkali metal silicate aqueous solution, 3-5 wt% of infiltration crystallization functional additive, and the balance of deionized water;

[0010] C) This repair material is not suitable when the crack width is greater than 0.4mm.

[0011] By adopting the above technical scheme, the width of the crack to be repaired can be classified, and different proportions of repair materials can be used according to the different crack widths. When the crack width is less than 0.2mm, the proportion of the alkali metal silicate aqueous solution of the crystallization component is reduced, and the amount of the retarding component in the infiltration crystallization functional additive is increased to extend the gel time of the repair material and allow the crystallization component to fully penetrate to a deeper place for crystallization. When the crack width is greater than 0.2mm and less than 0.4mm, the proportion of the alkali metal silicate aqueous solution of the crystallization component is increased, and the amount of the retarding component in the infiltration crystallization functional additive is reduced, the auxiliary crystallization component is increased, and the early strength component is increased to shorten the gel time of the repair material, promote the formation of more crystals, and improve the strength of the crystals, so that the repair material can quickly crystallize at the crack. When the crack width is greater than 0.4mm, it is difficult to repair such cracks due to the limitations of the material.

[0012] The present invention also provides a repair process for a wall using the wall crack repair material. According to different wall cracks, the repair process is divided into two cases:

[0013] (1) When strip cracks appear on the wall, the repair process includes the following steps:

[0014] S1: Clean the dust, dirt and loose parts on the wall surface around the cracks and rinse with water, and repair the defects with cement-based materials;

[0015] S2: A U-shaped plastic sealing strip is laid along the crack from the bottom to the top. The cut surface of the U-shaped plastic sealing strip is equipped with a suction cup, which is attached to the wall on both sides and below the crack. Waterproof glue is used to adhere the cut surface of the U-shaped plastic sealing strip to the wall surface where the wall surface is uneven.

[0016] S3: Inject clean water from the port of the U-shaped plastic sealing strip, check for leakage, and seal the leakage with waterproof glue in time;

[0017] S4: Inject the repair material from the port of the U-shaped plastic sealing strip, so that it gradually penetrates deep into the wall cracks under the action of gravity, and reacts with Ca(OH)2 in the concrete to crystallize and block the cracks;

[0018] S5: Regularly add repair material to the U-shaped plastic sealing strip, and remove the U-shaped plastic sealing strip after the liquid level stops dropping and the cracks are repaired.

[0019] (2) When radial cracks appear on the wall, the repair process includes the following steps:

[0020] S1: Clean the dust, dirt and loose parts on the wall surface around the cracks, and repair the defects such as pits and pits with cement-based materials;

[0021] S2: Soak the water-absorbing resin type curing film in the repair material and fully soak it for later use;

[0022] S3: Sprinkle water on the radial cracks on the wall to moisten them. After the surface is dry, apply the water-absorbing resin curing film that has been fully soaked with the repair material to the cracks and fix them. This allows the repair material to gradually penetrate deep into the cracks and gradually react and crystallize to block the cracks.

[0023] S4: Regularly add repair materials to the water-absorbent resin type curing film, and remove the water-absorbent resin type curing film after the cracks are repaired.

[0024] In the above technical scheme, the types of cracks to be repaired are classified, and different repair methods or a combination of two repair methods are adopted for strip cracks and radial cracks. When repairing wall cracks, first clean the wall surface at the crack, clean the dust, dirt and loose parts on the surface, and use cement-based materials to repair and level the defects such as roughness and pits. Then use U-shaped sealing strips, water-absorbing resin curing films or a combination of the two to repair the cracks or cracks on the wall. Finally, inspect the wall to confirm whether the repair is qualified. After the above repair process, the cracks on the wall can be repaired, and the repair method is convenient and fast, there is no color difference, and it does not affect the appearance of the wall. At the same time, the repair material remaining in the crack that has not reacted completely has the ability of secondary crystallization after film formation. When the cracks in this part expand or new cracks are generated later, it has an obvious crack self-repairing effect, which provides long-term protection for the concrete wall.

[0025] In the above technical scheme, floating dust, dirt, etc. on the cracks are cleaned, and the rough surfaces, pits, loose parts, etc. are pre-treated. First, to avoid the influence of debris on the crack repair effect, and second, the flat wall surface is conducive to the laying of U-shaped sealing strips and absorbent resin curing films, thereby improving the repair efficiency.

[0026] In the above technical solution, the wall strip cracks and the U-shaped plastic rubber sealing strip form a closed system. The plastic rubber sealing strip can be flexibly bent, which is convenient for the U-shaped sealing strip to be laid along the crack. The waterproof glue is applied as a supplementary material at the interface between the U-shaped sealing strip section and the wall surface to prevent the repair material from leaking out of the closed system. The penetration of the closed system is detected in advance, and the leakage is sealed with waterproof glue in time. The waste of repair materials is minimized and the repair efficiency is improved.

[0027] In the above technical solution, the water-absorbing resin type curing film is preferably a transparent water energy curing film, which is a commercially available product.

[0028] By adopting the above technical solution, small-scale radial cracks in the wall can be repaired. The water-absorbent resin curing film of the same size can be cut according to the size of the crack area. The water-absorbent resin gradually releases the repair material over a long period of time, so that the repair material can fully penetrate deep into the cracks to react and crystallize, and block the cracks.

[0029] Compared with the prior art, the present invention is beneficial in that:

[0030] 1. The repair material of the present invention has the functions of penetration crystallization and secondary crystallization, and can penetrate deep into the concrete cracks and penetrate 4 to 5 cm into the concrete, react chemically and physically with the alkaline substances, couple, and generate water-insoluble calcium silicate gel inside the concrete, thereby blocking the gaps, closing the capillary channels, and increasing the density;

[0031] 2. The present invention repairs concrete wall cracks by gravity grouting or continuous penetration and crystallization of water-absorbing resin. The penetrating substances in the material can penetrate deeper into the cracks and crystallize, gradually sealing the cracks from the inside out. The inorganic crystals can form an organic whole with the wall concrete, have the same lifespan as the structure, play a role of permanent waterproofing and anti-seepage, and do not affect the appearance of the concrete. Moreover, the repair material and repair process of the present invention can perform differentiated treatment on cracks of different widths and types, so as to achieve an ideal crack repair effect.

[0032] 3. For concrete wall cracks or cracks with a diameter of less than 0.4 mm, the present invention can adopt a method combining different repair processes and different repair materials to complete crack self-repair; at the same time, the viscosity and gelation time of the repair material of the present invention are adjustable, and the surface tension is significantly reduced. After the concrete specimens are soaked in the waterproof material of the present invention, the anti-permeability and anti-carbonization properties of the specimens are significantly improved, which can meet the standard requirements of JC / T 1018-2020.

[0033] 4. The U-shaped plastic rubber sealing strip and water-absorbing resin curing film of the present invention are both easily available construction materials, and the construction process is simple and feasible. It is only necessary to lay the sealing strip or the water-absorbing resin curing film on the construction site without drilling and grouting. The crack repair will not affect the appearance of the wall, and it is simple and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a front view of a U-shaped plastic rubber sealing strip;

[0035] Figure 2 for Figure 1 A transverse cross-sectional view in the AA direction;

[0036] Among them, 1 is the sealing strip body, 2 is the suction cup, and 3 is the internal cavity of the sealing strip, which is used for injecting repair materials. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the present invention and the following embodiments, taking the vertical crack on the wall as an example, the length direction of the U-shaped plastic rubber sealing strip is consistent with the crack direction, and the front view (i.e. Figure 1) The direction in which the observer looks toward the wall is taken as the viewing angle. The longitudinal section of the U-shaped plastic rubber sealing strip body (the longitudinal section of the U-shaped plastic rubber sealing strip, i.e., the section in the length direction faces the wall and is connected to the wall through the suction cup) is extended with a suction cup 2, so that it can be firmly adsorbed on the wall on both sides and below the crack through vacuum; the internal cavity enclosed between the sealing strip body and the wall is used to inject the repair material; moreover, the contact between the U-shaped plastic rubber sealing strip and the wall is sealed, and no additional sealing treatment is required during the construction process, which is convenient for construction.

[0039] In the following examples, the concentration of the sodium silicate aqueous solution is 30-40 wt %, the concentration of the potassium silicate aqueous solution is 30-40 wt %, and the concentration of the lithium silicate aqueous solution is 20-30 wt %.

[0040] Example 1

[0041] Repair the cracks in the wall of a municipal underground project. The wall thickness is 1300mm and the height is 6m. The cracks are penetrating cracks from top to bottom, and the widest crack is 0.2mm. The specific construction process is as follows:

[0042] S1: Clean the dust and dirt on the wall surface around the crack. The wall surface of the municipal underground project is flat and solid, and no surface repair work is required. After cleaning, use a marker to mark along the direction of the crack to facilitate the subsequent laying of the U-shaped plastic rubber sealing strip;

[0043] S2: Use a U-shaped plastic rubber sealing strip to lay it from the bottom to the top along the crack. Use its suction cup to vacuum the cut surface of the U-shaped sealing strip on the wall outside the crack. Use waterproof glue to firmly stick the wall on both sides and the bottom of the crack to the cut surface of the U-shaped plastic rubber sealing strip to prevent the repair material from spilling out.

[0044] S3: Inject clean water from the upper end of the U-shaped sealing strip to check for leakage, and use waterproof glue to seal the leakage;

[0045] S4: Inject the repair material from the upper end of the U-shaped sealing strip, 35% alkali metal silicate aqueous solution (including 20% ​​sodium silicate aqueous solution with a mass fraction of 35%, 10% potassium silicate aqueous solution with a mass fraction of 40%, and 5% lithium silicate aqueous solution with a mass fraction of 22%), 1% infiltration crystallization functional additive (including 0.6% EDTA-4Na, 0.2% triethanolamine, 0.1% citric acid, 0.08% sodium polyacrylate, and 0.02% sodium dodecylbenzene sulfonate), and 64% water. The repair material gradually penetrates deep into the wall cracks under the action of gravity, and reacts with Ca(OH)2 in the concrete to crystallize and block the cracks;

[0046] In this step, the repair material is prepared by mixing the corresponding proportions of the raw materials in the order of feeding: water, EDTA-4Na, citric acid, sodium polyacrylate, triethanolamine, sodium silicate aqueous solution, potassium silicate aqueous solution, lithium silicate aqueous solution, sodium dodecylbenzene sulfonate;

[0047] S5: Check the remaining amount of repair material in the U-shaped sealing strip on the 2nd, 4th and 7th day respectively and replenish it in time;

[0048] S6: After 14 days, check the crack repair status and remove the U-shaped sealing strip. After cleaning, it can be reused.

[0049] Example 2

[0050] Repair the cracks in the wall of a municipal underground project. The wall thickness is 1300mm and the height is 6m. The cracks are radial cracks that develop from top to bottom. The widest crack is 0.2mm. The specific construction process is as follows:

[0051] S1: Clean the dust and dirt on the wall surface within the radial crack area. The wall surface of the municipal underground project is flat and solid, and no surface repair work is required. After cleaning, use a marker to clearly mark the boundaries of the crack range in four directions, up, down, left and right, to facilitate the subsequent laying of the water-absorbing resin curing film;

[0052] S2: Soak the water-absorbing resin type curing membrane in the repair material and fully soak it for use, using the double-layer facade concrete curing membrane series YHM-SL product produced by Changsha Water Energy New Materials Co., Ltd. The repair material is the same as in Example 1;

[0053] S3: Sprinkle water on the radial cracks on the wall to moisten them. After the surface is dry, apply the YHM-SL water energy curing membrane that has been fully soaked with the above repair materials to the cracks and fix them. When paving, ensure that the curing membrane fits the wall surface fully, and no air permeable channels should be formed on the paving interface, otherwise the moisture in the water energy membrane will quickly dissipate and affect the repair effect. The repair material gradually penetrates from the water energy membrane into the depths of the wall cracks, and reacts with Ca(OH)2 in the concrete to crystallize and block the cracks;

[0054] S4: Check the remaining amount of repair material in the water energy curing film on the 3rd and 7th days respectively. If the water energy curing film becomes dry, remove it, soak it in the repair material again, and then stick it back to the original place;

[0055] S5: After 14 days, check the crack repair status and remove the water energy curing membrane.

[0056] Example 3

[0057] The content is basically the same as Example 1, except that the crack is a penetrating crack from top to bottom, and the widest crack is 0.4 mm wide. At the same time, the repair material ratio (mass percentage) is: 48% alkali metal silicate aqueous solution (including 25% sodium silicate aqueous solution with a mass fraction of 35%, 15% potassium silicate aqueous solution with a mass fraction of 40%, and 8% lithium silicate aqueous solution with a mass fraction of 22%), 1.7% penetration crystallization functional additive (including 0.6% EDTA-4Na, 1% triethanolamine, 0.08% sodium polyacrylate and 0.02% sodium dodecylbenzene sulfonate), and 50.3% water.

[0058] Example 4

[0059] The contents are basically the same as those in Example 2, except that the width of the crack at its widest point is 0.4 mm, and the repair material is the same as that in Example 3.

[0060] Comparative Example 1

[0061] The content is basically the same as that of Example 1, except that the crack is a penetrating crack from top to bottom, and the widest crack is 0.4 mm.

[0062] Comparative Example 2

[0063] The contents are basically the same as those in Example 2, except that the crack width at its widest point is 0.4 mm.

[0064] Comparative Example 3

[0065] The proportion of repair materials used in Example 1 and Example 2 is basically the same, except that no penetration crystallization functional additive is added. The specific proportion of repair materials (mass percentage) is: 35% alkali metal silicate aqueous solution, 65% water, wherein the alkali metal silicate aqueous solution includes 20% sodium silicate aqueous solution, 10% potassium silicate aqueous solution and 5% lithium silicate aqueous solution.

[0066] Comparative Example 4

[0067] The proportion of repair materials used in Example 3 and Example 4 is basically the same, except that no penetration crystallization functional additive is added. The specific proportion of repair materials (mass percentage) is: 48% alkali metal silicate aqueous solution, 52% water, wherein the alkali metal silicate aqueous solution includes 25% sodium silicate aqueous solution, 15% potassium silicate aqueous solution and 8% lithium silicate aqueous solution.

[0068] Table 1 shows the actual engineering repair effects of various embodiments and comparative examples.

[0069] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Repair effect / leakage no no no no yes yes

[0070] Note: After the wall cracks / cracks are repaired, check for leakage on the second day after heavy rain in the project area.

[0071] Test Example 2: Physical and Mechanical Properties Test of Repair Materials

[0072] According to the relevant provisions of JC / T 1018-2020 "Water-based Penetrating Inorganic Waterproofing Agent", the relevant physical and mechanical properties of the repair materials in Examples 1 to 4 and Comparative Examples 3 to 4 were determined, and the test results are shown in Table 2.

[0073] Table 2

[0074] Examples 1 and 2 Examples 3 and 4 Comparative Example 3 Comparative Example 4 Viscosity / s 10.2 12.8 10.1 12.5 Surface tension / (mN / m) 24.2 24.6 73.5 74.3 Gel time / min 160 60 170 65 Penetration height ratio / % 45.6 56.2 80.3 86.7 7d carbonization resistance value / % 53.2 49.2 26.1 23.2 28d carbonization resistance value / % 46.3 41.8 17.3 15.1

[0075] Note: The penetration height of the reference specimen (blank group) is 35 mm, the carbonization depth at 7 days is 7.2 mm, and the carbonization depth at 28 days is 15.3 mm.

[0076] It can be seen from the test results in Table 1 and Table 2 that for concrete wall cracks or cracks below 0.4 mm, a method combining different repair processes and different repair materials can be adopted to complete crack self-repair; at the same time, the viscosity and gelation time of the repair material of the present invention are adjustable, and the surface tension is significantly reduced. After the concrete specimens are immersed in the repair material of the present invention, the anti-permeability and anti-carbonization properties of the specimens are significantly improved.

[0077] By comparing Examples 1 and 3 with Comparative Example 1, it can be found that for through-wall cracks below 0.2 mm, the low-viscosity, high-retardation repair material has a better repair effect, but this component cannot repair through-wall cracks of 0.4 mm. When a high-viscosity, low-retardation repair material is used, it can better repair through-wall cracks of 0.4 mm. This shows that by combining the change of the repair material component with the wall crack repair process of the present invention, wall cracks of different widths below 0.4 mm can be effectively repaired. For radial cracks in the wall, by comparing Examples 2 and 4 with Comparative Example 2, it can be found that they have the same rules as the repair of wall cracks.

[0078] By comparing the physical and mechanical properties of the repair materials of Example 1 and Example 3, it can be found that compared with Example 1, the viscosity of the repair material in Example 3 is increased and the gelation time is greatly reduced, which allows the repair material to quickly crystallize on the surface of the crack, which is beneficial to improving the repair ability of wider cracks. The repair material in Example 1 has low viscosity and long gelation time, which allows the repair material to penetrate and crystallize deeper into the concrete cracks, which is beneficial to improving the repair ability of fine cracks or cracks. Compared with Example 1 and Example 3, Comparative Examples 3 and Comparative Examples 4 lack penetration and crystallization functional additives, and the surface tension of their repair liquids is significantly increased, which is not conducive to penetration and crystallization. The concrete's impermeability and carbonization resistance are also significantly reduced. The results cannot meet the standard requirements of JC / T1018-2020.

[0079] The above embodiments and comparative examples are only illustrative of the principles and effects of the present invention. A person skilled in the art may make several modifications and improvements without departing from the inventive concept of the present invention, and all of these belong to the protection scope of the present invention.

Claims

1. A wall crack repair material, characterized in that: It is a water-based penetrating inorganic waterproofing agent, which comprises, by mass percentage, 30-50wt% of an alkali metal silicate aqueous solution and 0.2-5wt% of a penetrating crystallization functional auxiliary agent, and the rest is water; wherein the alkali metal silicate aqueous solution is selected from at least two of a 30-40% sodium silicate aqueous solution, a 30-40% potassium silicate aqueous solution or a 20-30% lithium silicate aqueous solution; the penetrating crystallization functional auxiliary agent comprises, by mass percentage, 55-65% tetrasodium ethylenediaminetetraacetate, 15-25% triethanolamine, 5-15% citric acid, 6-10% sodium polyacrylate and 1-3% sodium dodecylbenzene sulfonate; the width of the wall crack does not exceed 0.4mm; When the crack width is less than 0.2 mm, the wall crack repair material comprises, by mass percentage, 30-40 wt % of an alkali metal silicate aqueous solution and 0.2-4 wt % of a penetration crystallization functional additive, and the remainder is deionized water; When the crack width is greater than 0.2 mm and less than 0.4 mm, the wall crack repair material comprises, by mass percentage: 40-50 wt % of alkali metal silicate aqueous solution and 3-5 wt % of penetration crystallization functional additive, and the rest is deionized water.

2. The application of the wall crack repair material according to claim 1 in wall repair, characterized in that: When the wall cracks are strip cracks, the repair process using the wall crack repair material includes the following steps: S1: Clean the dust, dirt and loose parts on the wall surface around the cracks and rinse with water, and repair the defects with cement-based materials; S2: A U-shaped plastic sealing strip is laid along the crack from the bottom to the top. The cut surface of the U-shaped plastic sealing strip is equipped with a suction cup, which is attached to the wall on both sides and below the crack. Waterproof glue is used to adhere the cut surface of the U-shaped plastic sealing strip to the wall surface where the wall surface is uneven. S3: Inject clean water from the port of the U-shaped plastic sealing strip, check for leakage, and seal the leakage with waterproof glue in time; S4: Inject the repair material from the port of the U-shaped plastic sealing strip, so that it gradually penetrates deep into the wall cracks under the action of gravity, and reacts with Ca(OH)2 in the concrete to crystallize and block the cracks; S5: Regularly add repair material to the U-shaped plastic sealing strip, and remove the U-shaped plastic sealing strip after the liquid level stops dropping and the cracks are repaired.

3. The use according to claim 2, characterized in that: The U-shaped plastic sealing strip is made of rubber; a suction cup is extended from the longitudinal section of the U-shaped plastic sealing strip for adsorbing on the walls on both sides and below the crack, and the internal cavity of the sealing strip is used for injecting repair materials.

4. The application of the wall crack repair material according to claim 1 in wall repair, characterized in that: When the wall cracks are radial cracks, the repair process using the wall crack repair material includes the following steps: S1: Clean the dust, dirt and loose parts on the wall surface around the cracks, and repair the defects with cement-based materials; S2: Soak the water-absorbing resin type curing film in the repair material and fully soak it for later use; S3: Sprinkle water on the radial cracks on the wall to moisten them. After the surface is dry, apply the water-absorbing resin curing film that has been fully soaked with the repair material to the cracks and fix them. This allows the repair material to gradually penetrate deep into the cracks and gradually react and crystallize to block the cracks. S4: Regularly add repair materials to the water-absorbent resin type curing film, and remove the water-absorbent resin type curing film after the cracks are repaired.

5. The use according to claim 4, characterized in that: The water-absorbing resin type curing film shown is a transparent water energy curing film.